2023
DOI: 10.3390/land12101892
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Farmers’ Cognition on Forest Land Transfer Behavior: A Case Study of Chengdu City

Ying Cheng,
Zhongbao Liu,
Yuan Hu
et al.

Abstract: In the context of China’s forest rights reform, promoting forest land circulation is the key to revitalizing forest land resources and promoting the development of the forestry industry. Based on the theoretical analysis of the effect of farmers’ cognition on forest land transfer behavior, data from 790 farmers in typical areas of Chengdu were used for empirical testing with the binary logit model. At the same time, the effects of the cognitive differences of the farmers with different education levels on fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…For example, the land transfer effect of non-farm employment differs according to the gender of the employee [28], while the distance from employment also plays a crucial role in land transfer decisions [29]. Another strand of research focuses on micro-characteristics such as households, household heads, and communities [7,30,31]. Moreover, institutional arrangements such as land ownership reform and public pension schemes significantly impact land transfer [6,32].…”
Section: Research Backgroundmentioning
confidence: 99%
“…For example, the land transfer effect of non-farm employment differs according to the gender of the employee [28], while the distance from employment also plays a crucial role in land transfer decisions [29]. Another strand of research focuses on micro-characteristics such as households, household heads, and communities [7,30,31]. Moreover, institutional arrangements such as land ownership reform and public pension schemes significantly impact land transfer [6,32].…”
Section: Research Backgroundmentioning
confidence: 99%
“…By combing through the relevant literature, it is easy to find that current research on farmers' land transfer behavior mainly focuses on the scale of land transfer [16], land transfer mode [14], land transfer system reform [31], land transfer willingness and behavior [32][33][34][35], factors influencing land transfer behavior [36][37][38], land transfer performance [31,39], etc. Through analysis, it can be found that scholars have carried out richer research on land transfer behavior, which clearly shows that land transfer has changed the relationship between farmers and land.…”
Section: Introductionmentioning
confidence: 99%